Democracy and Deliberation: A Case Study of Deliberation on Draft Constitution - Ruttanasatain, Ngamsuk; Saisaeng, Bordin (Political Science Critique, 2025)
This research aims on studying concepts and formats of deliberative democracy in various aspects, especially in term of process that would be suitable for development of culture of deep listening and result-based deliberation. In conducting this research, both qualitative and participatory methodologies were used in order to experiment the usefulness of deliberative dialogue in clarifying some particular conflicted issues from the draft of constitution. The findings of this research are shown as follows; 1) in the contextual aspect regarding problem of Thai democracy, it is found that, a constitution either in the contexts or the drafting process and political power relation reflexes the issue of democratic value and protracted social conflict in Thailand, and 2) on the process context, it is found that, the utilization of “issue book” is the key instrument in deliberative dialogue process.